MEMAHAMKAN PENGETAHUAN AKUNTANSI DI TINGKAT PENGANTAR - Suwardjono Suwardjono (Journal of Indonesian Economy and Business (JIEB), 1999)
Introducing a new knowledge to new students is not an easy task. Dysfunctionalbehaviors may result due to inappropriate approach to introducing the newknowledge. Introducing accounting to beginners is no difference. This paperdescribes an alternative strategy to improve introductory accounting learning andteaching in higher education institutions. The author argues that some dysfunctionalbehaviors related to understanding accounting are attributed to the way thisknowledge is introduced to new students. Instructors tend to emphasize heavily on thetechnical aspects of accounting without incorporating the conceptual and theoreticalideas behind the technical process. More importantly, the fact that accounting is abody of knowledge is often left in the introduction so that nonaccounting studentshave the wrong ideas about accounting. Accounting is often viewed as a merelytechnical recording rather than a challenging knowledge that calls for intellectualand scientific inquiries. This paper provides a framework of how theoretical aspectsof accounting are introduced to new students as a basis for explaining the technicalprocess of accounting. These theoretical aspects are summarized in the form ofaccounting structure to help students understand accounting in a broad sense.Institutional and instructional policies regarding the introductory accounting courseare also discussed.